Gender in the Middle East & North Africa contemporary issues and challenges - Ryan, J. Michael; Rizzo, Helen Mary (Lynne Rienner Publishers, 2020)
"The role of gender in the Middle East and North Africa is widely discussed-but often little understood. Seeking to close that gap, the authors of this comprehensive study explore a wide range of issues related to gender in the region as they have been unfolding since the Arab Spring"--
Keywords: Geschlechterrolle; Soziale Situation; Frau; Nordafrika; Naher Osten; Women / Middle East / Social conditions / 21st century; Women / Africa, North / Social conditions / 21st century; Sex role / Middle East; Sex role / Africa, North; Aufsatzsammlung